Weierstrass's Non-Differentiable Function

Weierstrass's Non-Differentiable Function

Weierstrass’s non-differentiable function Jeff Calder December 12, 2014 In the nineteenth century, many mathematicians held the belief that a continuous function must be differentiable at a large set of points. In 1872, Karl Weierstrass shocked the mathe- matical world by giving the first published example of a continuous function that is nowhere differentiable. His function is given by 1 X W (x) = an cos(bnπx): n=0 In particular, Weierstrass proved the following theorem: Theorem 1 (Weierstrass 1872). Let a 2 (0; 1), let b > 1 be an odd integer, and assume that 3 ab > 1 + π: (1) 2 Then the function W is continuous and nowhere differentiable on R. To see that W is continuous on R, note that jan cos(bnπx)j = anj cos(bnπx)j ≤ an: Since the geometric series P an converges for a 2 (0; 1), the Weierstrass M-test shows that n n the series defining W converges uniformly to W on R. Since each function a cos(b πx) is continuous, each partial sum is continuous, and therefore W is continuous, being the uniform limit of a sequence of continuous functions. To give some motivation for the condition (1), consider the partial sums n X k k Wn(x) = a cos(b πx): k=0 These partial sums are differentiable functions and n 0 X k k Wn(x) = − π(ab) sin(b πx): k=0 0 If ab < 1, then we can again use the Weierstrass M-test to show that (Wn) converges uniformly to a continuous function on R. In this case we can actually prove that W is differentiable 0 0 and Wn ! W uniformly. Therefore, at the very least we need ab ≥ 1 for W to be non- differentiable. In 1916, Godfrey Hardy showed that ab ≥ 1 is sufficient for the nowhere 1 2 2 1.5 1.8 1 1.6 0.5 0 1.4 −0.5 1.2 −1 1 −1.5 −2 0.8 −1 −0.5 0 0.5 1 −0.1 −0.05 0 0.05 0.1 (a) (b) Figure 1: The Weierstrass function W (x) for a = 0:5 and b = 3. Notice that W appears the same on the two different scales shown in (a) and (b). 3 differentiability of W . The more restrictive condition ab > 1 + 2 π present in Weierstrass’s proof is an artifact of the techniques he used. Hardy also relaxed the integral assumption on b, and allowed b to be any real number greater than 1. Figure1 shows a plot of the Weierstrass function for a = 0:5 and b = 3 on two different scales. Notice the similar repeating patterns on each scale. If we were to continue zooming in on W , we would continue seeing the same patterns. The Weierstrass function is an early example of a fractal, which has repeating patterns at every scale. Before giving the proof, we recall a few facts that will be useful in the proof. Let x; y 2 R, and suppose x > y. Then by the fundamental theorem of calculus Z x Z x cos(x) − cos(y) = − sin(t) dt ≤ 1 dt = x − y; y y and Z x cos(x) − cos(y) ≥ −1 dt = −(x − y): y Therefore j cos(x) − cos(y)j ≤ jx − yj: The argument is similar when y ≥ x, so we deduce j cos(x) − cos(y)j ≤ jx − yj for all x; y 2 R: (2) Consider cos(nπ + x) for an integer n and x 2 R. If n is even, then since cosine is 2π-periodic, cos(nπ + x) = cos(x). If n is odd, then n + 1 is even and cos(nπ + x) = cos((n + 1)π + x − π) = cos(x − π) = − cos(x): Draw a graph of cos(x) if the last equality is unclear. Therefore we obtain n cos(nπ + x) = (−1) cos(x) for all x 2 R: (3) We now give the proof of Theorem1. 2 m Proof. Let x0 2 R and let m 2 N. Let us round b x0 to the nearest integer, and call this integer km. Therefore 1 1 bmx − ≤ k ≤ bmx + : (4) 0 2 m 0 2 Let us also set k + 1 x = m : (5) m bm By (4) we see that m 1 m b x0 − 2 + 1 b x0 xm ≥ m > = x0; b bm and m 1 b x0 + + 1 3 x ≤ 2 = x + : m bm 0 2bm Combining these equations we have 3 x < x ≤ x + : (6) 0 m 0 2bm By the squeeze lemma, limm!1 xm = x0. Let us consider the difference 1 1 X n n X n n W (xm) − W (x0) = a cos(b πxm) − a cos(b πx0) n=0 n=0 1 X n n n = a (cos(b πxm) − cos(b πx0)) n=0 = A + B; (7) where m−1 X n n n A = a (cos(b πxm) − cos(b πx0)) ; (8) n=0 and 1 X n n n B = a (cos(b πxm) − cos(b πx0)) : (9) n=m The proof is now split into three steps. 1. The first step is to find an upper bound for jAj. Using the triangle inequality and the identity (2) m−1 m−1 m−1 X n n n X n n X n jAj ≤ a jcos(b πxm) − cos(b πx0)j ≤ a b π(xm − x0) = π(xm − x0) (ab) : n=0 n=0 n=0 Noticing the geometric series, we deduce 1 − (ab)m (ab)m − 1 π(ab)m jAj ≤ π(x − x ) = π(x − x ) ≤ (x − x ): (10) m 0 1 − ab m 0 ab − 1 ab − 1 m 0 3 In the last step we used the hypothesis that ab > 1 + 2 π > 1. 3 2. The second step is to find a lower bound for jBj. By the definition of xm (5) k + 1 cos(bnπx ) = cos bnπ m = cos(bn−m(k + 1)π): m bm m n−m For n ≥ m, b (km + 1) is an integer, and hence n−m n−m km+1 n b (km+1) b km+1 km cos(b πxm) = (−1) = (−1) = (−1) = −(−1) ; (11) where we used the fact that bn−m is odd so that (−1)bn−m = −1. On the other hand, we also have k + bmx − k cos(bnπx ) = cos bnπ m 0 m = cos(bn−mk π + bn−mz π); 0 bm m m m n−m where zm = b x0 − km. Since n ≥ m, b km is an integer and we can use (3) to find that n−m n b km n−m km n−m cos(b πx0) = (−1) cos(b zmπ) = (−1) cos(b zmπ); (12) where, as before, we used the fact that bn−m is odd. We now insert (11) and (12) into (9) to obtain 1 X n km km n−m B = a −(−1) − (−1) cos(b zmπ) n=m 1 km X n n−m = −(−1) a 1 + cos(b zmπ) : n=m n n−m Notice that a > 0 and 1 + cos(b zmπ) ≥ 0. It follows that all the terms in the sum above are non-negative, and therefore 1 X n n−m m jBj = a 1 + cos(b zmπ) ≥ a (1 + cos(zmπ)) : n=m m 1 1 π π Recall that zm = b x0 − km. By (4), zm 2 [− 2 ; 2 ], and therefore πzm 2 [− 2 ; 2 ]. It follows that cos(zmπ) ≥ 0 and jBj ≥ am: 3 By (6), xm − x0 ≤ 2bm , and thus 2bm (x − x ) ≤ 1: 3 m 0 We can combine this with jBj ≥ am to find that 2(ab)m jBj ≥ am · 1 ≥ (x − x ): (13) 3 m 0 This is the desired lower bound on jBj, and completes part 2 of the proof. 3. We now combine the bounds (10) and (13) to complete the proof. Notice by (10), (13) and the reverse triangle inequality that 2(ab)m π(ab)m 2 π jA + Bj ≥ jBj − jAj ≥ (x − x ) − (x − x ) = (ab)m − (x − x ): 3 m 0 ab − 1 m 0 3 ab − 1 m 0 4 By (7) we see that 2 π jW (x ) − W (x )j = jA + Bj ≥ (ab)m − (x − x ): m 0 3 ab − 1 m 0 Since xm − x0 > 0, so that jxm − x0j = xm − x0, we have W (xm) − W (x0) m 2 π ≥ (ab) − : (14) xm − x0 3 ab − 1 We would like this difference quotient to tend to 1 in absolute value as m ! 1. For this we need ab > 1 and 2 π − > 0: 3 ab − 1 Rearranging this for ab we see that we need 3 ab > π + 1; 2 which is exactly the hypothesis (1). Therefore W (xm) − W (x0) lim = +1; m!1 xm − x0 and xm ! x0 as m ! 1. This shows that W is not differentiable at x0. With slight modifications to the proof, we can also show that W (x) − W (x ) lim 0 x!x0 x − x0 does not exist as a real number or ±∞. This rules out the possibility of the Weierstrass function having a vertical tangent line, or an “infinite derivative” anywhere. 5.

View Full Text

Details

  • File Type
    pdf
  • Upload Time
    -
  • Content Languages
    English
  • Upload User
    Anonymous/Not logged-in
  • File Pages
    5 Page
  • File Size
    -

Download

Channel Download Status
Express Download Enable

Copyright

We respect the copyrights and intellectual property rights of all users. All uploaded documents are either original works of the uploader or authorized works of the rightful owners.

  • Not to be reproduced or distributed without explicit permission.
  • Not used for commercial purposes outside of approved use cases.
  • Not used to infringe on the rights of the original creators.
  • If you believe any content infringes your copyright, please contact us immediately.

Support

For help with questions, suggestions, or problems, please contact us